PENGARUH PENEMPATAN PEGAWAI DAN KARAKTERISTIK INDIVIDU TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR CAMAT RENGAT BARAT KABUPATEN INDRAGIRI HULU - Marisca, Risanty (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was conducted at the Rengat Barat Sub-District Office Indragiri Hulu Regency which lasts approximately 6 (six) months. Formulation of the problem is whether the placement of employees and characteristics individuals simultaneously have a significant effect on employee performance. The purpose of the study was to determine the effect of employee placement and simultaneous individual characteristics of employee performance.In this study, the authors used sampling with census method, which is a sample of 37 respondents. Data analysis used in this study namely descriptive analysis and quantitative analysis.The results of Multiple Linear Regression Analysis obtained Y = 3.805 + 0.924 X 1 + 0.077 X 2 a = 3.805 means if the placement of employees and individual characteristics equal to 0 (zero), the amount of work performance is 3.805 points, b1 = 0.924 meaning if the placement of employees increases by 1 (one) unit (temporary fixed individual characteristics) then work performance will increase amounting to 0.924 points, b2 = 0.077 means if individual characteristics increase amounting to 1 (one) unit (temporary placement of permanent employees) then achievement employment will increase by 0.077 points. Simultaneous Test Results (Test F) obtained F count 26,622 & gt; F table 3.28, then based on data testing criteria it can be seen that H a is accepted and H 0 is rejected, which means the placement of employees and individual characteristics together (simultaneous) influence significant work performance. The results of the R test calculation, obtained by the value of R or correlation is 0.781 meaning having a strong and direct relationship between the placement of employees and individual characteristics with work performance, that means if the placement of employees and individual characteristics increases then work performance will also increase and the value of R Square or The coefficient of determination (R2) of 0.610 means that the work performance variable can be explained by variable placement of employees and individual characteristics of 61%, while the remaining 39% is explained by independent variables others not examined